STATE AND PROSPECTS OF WIND ENERGY AS A FACTOR OF UKRAINE’S ECONOMIC DEVELOPMENT - Cherevko І.; Hrynchuk Р. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The purpose of the research was to study and systematize the economic, ecological and technological advantages and disadvantages of wind energy and the conditions, opportunities and problems of its development in Ukraine as a factor of the country’s economic development in the conditions of war. The methodology of the conducted research is based on the application of the descriptive-analytical method in the process of studying the phenomena and processes, that are taking place in the energy base of the countries of the world and, in particular, in Ukraine, which is combined with the organic synthesis of the results obtained due to the application of the descriptive-analytical method of the results, their systematization and generalization, as well as with the comparative method, which turned out to be particularly suitable in the process of analyzing the trends in the development of wind energy in Ukraine. It is established that wind power has significant technological, economic and environmental advantages over other branches of renewable energy, but it also has certain disadvantages. The comparative analysis showed that the total assessment of the advantages of wind energy is much higher than the total assessment of its disadvantages, which, by the way, decreases over time as the relevant technologies progress. The rate of wind energy development in the pre-war period in Ukraine was also quite high, and even during the war, it continued to develop. Ukraine is intensively rebuilding destroyed wind energy facilities, actively building a network of new wind power plants on controlled territories, as there is an understanding of the need to start rebuilding the economy without waiting for victory, and that it should start with wind power, which can significantly reduce and eliminate the energy deficit in the country relatively quickly. The main factors that will influence the scenario of liquidation of the consequences of russian military aggression in the wind energy industry of Ukraine and its post-war reconstruction are the time and conditions of the end of the war, the pace of recovery, and forecasting indicators of GDP growth, the rate and completeness of market integration with the EU, the quality of the state support for wind energy in terms of creating favorable economic conditions for it, since favorable natural conditions for the development of wind power industry in Ukraine are objectively available.